Efficacy evaluation of hepato and nephroprotective properties of Ethanolic Withania sominifera root extract (EWRE) against rotenone induced toxicity in male Wistar rats - Epuri, Vishala; Kumar, Ravi; R. Praveen Kumar, Doni.; Madhav, G. Venu (Journal of Neonatal Surgery, 2025)
Rotenone is a lipophilic natural compound mostly obtained from the roots and stems of Lonchocarpus and Derris species used as a pesticide and known as mitochondrial respiratory chain complex I inhibitor as a result ATP production stops and activates reactive oxygen and nitrogen species leading to neurodegeneration by apoptosis. Acute exposure to 2mg/kg/b.wt of Rotenone (Rot) to males rats is proven to be cytotoxic and induces histological alternations in soft tissues. Withania somnifera (WS) is a versatile multifaceted medicinal herb which exhibits anti-cancer, anti-aging, anti-diabetic, anti-oxidative and anti-inflammatory responses. The present study reports the hepato and nephroprotective properties of Ethanolic Withania sominifera root extract (EWRE) and other cytoprotectants against Rotenone induced histological change liver and kidney tissue of male Wistar rats (n=45). The experiment rats were divided into 9 groups (Group I: Control, Group II: 2mg/kg/b.wt Rotenone treated, Group III: 100 mg/kg.bw EWRE, Group IV: 40mg/kg/b.wt Doxycycline; Group V: 40mg/kg/b.wt Ellagic acid; Group VI: 2mg/kg/b.wt Rotenone-100mg/kg/b.wt EWSR; Group VII: 2mg/kg/b.wt Rotenone-40mg/kg/b.wt Doxy; Group VIII: 2mg/kg/b.wt Rotenone-40mg/kg/b.wt Ellagic acid; Group IX: 2mg/kg/b.wt Rotenone-EWSR-Doxy-EA. Rats from group 2, 6-9 received 2mg/kg/b.wt Rotenone (Rot) for 4 weeks and later they were treated with 100 mg/kg./b.wt of EWRE (orally); 40mg/kg/b.wt doxycycline; and 40mg/kg/b.wt Ellagic acid (Intraperitoneally) individually and in combination for 40 days and on day 70 rat were sacrificed by cervical dislocation. Histomorphology of liver and kidney was assessed by H&E stain. Our results suggests that acute exposure of Rot in adult rats caused detrimental effects in the liver and kidney. The Rotenone induced cytotoxicity was ameliorated with EWRE administration, i.e. 100 mg of EWRE showed better reversal efficiency than 40 mg of Doxycycline and Ellagic acid individually and combination.